REPRESENTASI GENDER TOKOH DIANA DALAM FILM WONDER WOMAN - Retno Indriyani; Yuliana Rakhmawati (SEMIOTIKA: Jurnal Komunikasi, 2018)
ABSTRACTThe purpose of this study is to describe feminism in the female film Superhero entitled'Wonder Woman' which was released in 2017 and to find out the implicit meaning of feminism.This research uses qualitative and descriptive methods and semiotic analysis of Roland Barthes.Roland Barthes's semiotic analysis includes denotation (true meaning) and connotation (doublemeaning, born from cultural and personal experiences). And if the connotation is inherent insociety, it will become a myth. The analysis of this research is based on the elements ofnarrative films, such as space and time, character, conflict, and purpose. The results obtainedfrom this study are from 14 selected scenes in this Wonder Woman film containing 4 points offeminism. The feminism point was taken based on a book called Feminist Thought by RosemariePutnam Tong. Feminism consists of feminism in struggle, feminism in making decision,feminism in the power of determination, and feminism in love. Wonder Woman is amonoandrogynous woman, where she shows feminine and masculine character at the sametime. Beautiful, innocent, compassionate, eager for the opposite sex, can fall in love like womenin general. But at the same time also aggressive, can lead, can compete, can make their owndecisions and can carry responsibility for the interests of many people like men.Keywords: Feminism, Movie, Wonder Woman, Gender Communication, Roland Barthes’sSemioticsABSTRAKTujuan dari penelitian ini adalah untuk mendeskripsikan feminisme yang ada dalam FilmSuperhero wanita berjudul „Wonder Woman‟ yang dirilis pada tahun 2017 serta untuk mengetahui maknayang tersirat dari feminisme tersebut. Penelitan ini menggunakan metode kualitatif dan deskriptif sertaanalisis semiotika Roland Barthes. Analisis semiotika Roland Barthes mencakup denotasi (maknasebenarnya) dan konotasi (makna ganda, yang lahir dari pengalaman kultural dan pribadi). Dan jikakonotasi sudah melekat dalam masyarakat, maka akan menjadi mitos. Analisis penelitian ini berpokokpada elemen-elemen film naratif, seperti ruang dan waktu, tokoh, konflik, dan tujuan. Hasil yang didapatdari penelitian ini adalah dari 14 adegan terpilih yang ada di film Wonder Woman ini mengandung 4 poinfeminisme. Poin feminisme tersebut diambil berdasarkan buku berjudul Feminist Thought oleh Tong.Feminisme tersebut terdiri dari feminisme dalam perjuangan, feminisme dalam pengambilan keputusan,feminisme dalam kekuatan tekad, dan feminisme dalam kasih sayang. Wonder Woman adalah perempuanyang monoandrogini, yaitu di mana ia menunjukkan karakter feminin dan maskulin pada saat yangbersamaan. Cantik, polos, penyayang, berhasrat untuk lawan jenis, dapat jatuh cinta seperti perempuanpada umumnya. Namun di waktu yang sama juga agresif, dapat memimpin, dapat bersaing, dapatmengambil keputusannya sendiri dan dapat mengemban tanggung jawab untuk kepentingan orang banyaklayaknya laki-laki.Kata Kunci: Feminisme, Film, Wonder Woman, Komunikasi Gender, Semiotika Roland Barthes